MODEL PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN KEMAMPUAN BICARA PADA PEMBELAJARAN BAHASA INGGRIS - Susilowati, Sumaryani Rita; Atikah, Cucu; Rusdiyani, Isti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
A useful cooperative learning model is an instructional strategy where students collaborate in small groups to achieve shared learning objectives. This method allows students to practice asking questions, discussing issues, examining cases, learning leadership skills, and actively participating in discussions with their peers. This study aims to assess the effectiveness of this engaging learning model in improving students' English-speaking skills. The exploration was conducted with class VII C at SMP Negeri 2 Rangkasbitung, involving 32 participants, consisting of 16 boys and 16 girls. The strategy used is a quantitative methodology with a quasi-experimental plan and a one-group pre-test and post-test design. A pre-test was administered before the treatment, and a post-test was given after the treatment to measure changes in the students' speaking abilities. The review results show that the cooperative learning model effectively improves students' speaking skills. There was a 33.77% increase in scores between the pre-test and post-test data. Through dynamic associations and group discussions, students have more opportunities to speak, listen, and practice English effectively. Consequently, the collaborative learning model enhances students' speaking skills, social interaction abilities, and active participation in learning. The review implies that the engaging learning model can significantly improve speaking skills.